Struggles of immigration at the doorstep of Irish education: the historical perspectives of Irish and international pupils in secondary schools in Ireland - Garrison, Mathew James (Trinity College (Dublin, Ireland). School of Education, 2009)
In recent years, due to economic prosperity and globalization, Ireland has experienced an influx of immigration. Not only have many Irish people returned, but a large number of immigrants from culturally and ethnically diverse countries have landed on Irish shores. This has transformed the cultural background, ethnicity and religion of the student body in many Irish schools and has the potential to change the national curriculum of many subjects at the primary and secondary level. One subject that is potentially affected by an increase of cultural, social and ethnically diverse perspectives is the teaching of history. A sociocultural perspective on learning history assumes that individuals actively engage in the historical practices of their society. Individuals engage with history through a variety of sources, such as family, local community and ethnic groups. Understanding how and why individuals engage with these and many other sources of history is important in understanding the social and cultural backgrounds of pupils in the process of everyday life. It points to the importance of understanding the social and cultural backgrounds of pupils in the process of better understanding how they think about history and, more importantly, how they use history as a cultural tool in their mediation in everyday life. This research included 372 secondary level pupils (n = 265 Irish pupils, n = 107 International pupils) in 7 schools in the greater Dublin city area.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin